2018
DOI: 10.3389/fnagi.2018.00282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Physical and Cognitive Virtual Reality-Based Training on Cognitive Impairment and Oxidative Stress in MCI Patients: A Pilot Study

Abstract: The growing elderly population and the increased incidence of mild cognitive impairment (MCI) and Alzheimer’s disease (AD) call for the improvement of the quality and the efficacy of the healthcare and social support services. Exercise and cognitive stimulation have been demonstrated to mitigate cognitive impairment and oxidative stress (OxS) has been recognized as a factor that contributes to the advancement of neurodegenerative diseases. Taking these aspects into account, the impact of a novel virtual realit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(158 citation statements)
references
References 55 publications
3
155
0
Order By: Relevance
“…The exergames in 5 studies were implemented on sensor-based platforms [ 50 , 67 , 68 , 71 , 72 ] such as Nintendo Wii-Fit and FitForAll; 4 studies used video camera systems such as Xbox 360 Kinect, X-Torp, and Bike Labyrinth to capture physical movements [ 52 , 66 , 69 , 70 ]; and another study used a handheld controller [ 45 ]. The interventions were administered by a researcher [ 45 , 50 , 68 - 70 , 72 ], therapist [ 66 ], clinical doctor [ 52 ], and family caregiver [ 71 ]. In the study of Bamidies et al [ 67 ], the intervention was carried out in a group setting with psychologists, physical education instructors, researchers, or nurses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exergames in 5 studies were implemented on sensor-based platforms [ 50 , 67 , 68 , 71 , 72 ] such as Nintendo Wii-Fit and FitForAll; 4 studies used video camera systems such as Xbox 360 Kinect, X-Torp, and Bike Labyrinth to capture physical movements [ 52 , 66 , 69 , 70 ]; and another study used a handheld controller [ 45 ]. The interventions were administered by a researcher [ 45 , 50 , 68 - 70 , 72 ], therapist [ 66 ], clinical doctor [ 52 ], and family caregiver [ 71 ]. In the study of Bamidies et al [ 67 ], the intervention was carried out in a group setting with psychologists, physical education instructors, researchers, or nurses.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Bamidi et al [ 67 ], a group of psychologists, physical education instructors, researchers, and nurses helped each elderly person design a plan that included aerobic, resistance, and strength exercises. However, due to the small sample size, short intervention duration [ 70 - 72 ], and lack of specific exercises [ 72 ], a positive result was not obtained in several other preliminary experiments [ 50 , 70 - 72 ]. In addition, some studies reported “small” to “moderate” effect sizes for the cognitive function results [ 50 , 52 , 72 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of using VR interventions include enhancing accessibility and cost-effectiveness, creating an immersive experience, and providing immediate feedback based on an individual’s performance. Previous articles have shown positive effects of these VR interventions on attention and visual and verbal memory, as well as executive functioning, in older adults with MCI (Coyle et al, 2015; Mrakic-Sposta et al, 2018). Due to the advantages of VR, integrating physical and cognitive training into VR appears to be a good intervention approach.…”
Section: Introductionmentioning
confidence: 97%
“…Several factors appear to affect endothelial dysfunction, and different strategies have been proposed to change these factors and counteract it. Other than conventional drug therapies, lifestyle and dietary interventions are majorly encouraged, especially in age-related vascular endothelial dysfunction [ 198 ]. For example, regular exercise and caloric restriction can exert beneficial effects increasing NO bioavailability, eNOS, and SOD activity, as well as reducing oxidative stress, cholesterol, and systolic blood pressure.…”
Section: New Therapeutic Approaches Targeted Endothelial Dysfunctimentioning
confidence: 99%